2024
DOI: 10.1002/jeab.915
|View full text |Cite
|
Sign up to set email alerts
|

Comparing stimulus preference and response force in a conjugate preparation: A replication with auditory stimulation

Jennifer L. Cook,
Rasha R. Baruni,
Jonathan W. Pinkston
et al.

Abstract: This study examined a conjugate approach for evaluating auditory stimulus preference for 81 participants using force as a continuous response dimension. First, the researchers used a verbal preference assessment to evaluate each participant's preference for listening to five genres of music. This process identified high‐preference and low‐preference music for each participant. Thereafter, the researchers exposed each participant to the five music genres in a randomized order while using a hand dynamometer to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…As this study was a replication and extension of Davis et al (2021), andCook et al (2024) to a degree, the apparatus was similar. The researchers used custom software written in Labview (NI, Austin, TX, USA) for programming events and data collection.…”
Section: Apparatusmentioning
confidence: 99%
See 4 more Smart Citations
“…As this study was a replication and extension of Davis et al (2021), andCook et al (2024) to a degree, the apparatus was similar. The researchers used custom software written in Labview (NI, Austin, TX, USA) for programming events and data collection.…”
Section: Apparatusmentioning
confidence: 99%
“…Software sampled forces from the dynamometer at 20 samples per second and reported the average and maximal force obtained for each 20-sample window. Previous tests with the dynamometer indicated that it naturally fluctuated by 0.1 kg around zero even at rest (Cook et al, 2024;Davis et al, 2021). The program implemented a progressive schedule whereby response criteria were updated second by second.…”
Section: Apparatusmentioning
confidence: 99%
See 3 more Smart Citations